1974
DOI: 10.1128/jb.117.2.619-630.1974
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Nature of Two Nonconjugative Plasmids Carrying Drug Resistance Genes

Abstract: SuSm and N-Tc, have been characterized. Both were of relatively small size (5 x 106 to 6 x 106 daltons) and present in multiple copies within their respective bacterial hosts. N-SuSm possessed a guanine plus cytosine content of 55%, whereas N-Tc was 49% guanine plus cytosine. Although these plasmids were inherently nontransmissible they could be mobilized by a large variety of transfer agents including Ent, Hly, and K88. The fih transfer factors tested were far more likely (about 200x) to mobilize these noncon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(67 citation statements)
references
References 39 publications
1
66
0
Order By: Relevance
“…To determine whether the destabilizing effect of DpiA overexpression is restricted to pSC101, we tested plasmids carrying other replicons. We found that the mini-F plasmid pMF21 (Kline and Trawick, 1983) and a R6K derivative (pRR15, Roberts et al, 1990) were also strongly destabilized by pHI1447; however, the stability of a P1 plasmid derivative (pALA110, Abeles et al, 1985), the broad host range plasmid RSF1010 (Guerry et al, 1974) and the ColD derivative, pGZ119 (Lessl et al, 1992), was not affected ( Table 1).…”
Section: Dpia Affects Plasmids Other Than Psc101mentioning
confidence: 91%
“…To determine whether the destabilizing effect of DpiA overexpression is restricted to pSC101, we tested plasmids carrying other replicons. We found that the mini-F plasmid pMF21 (Kline and Trawick, 1983) and a R6K derivative (pRR15, Roberts et al, 1990) were also strongly destabilized by pHI1447; however, the stability of a P1 plasmid derivative (pALA110, Abeles et al, 1985), the broad host range plasmid RSF1010 (Guerry et al, 1974) and the ColD derivative, pGZ119 (Lessl et al, 1992), was not affected ( Table 1).…”
Section: Dpia Affects Plasmids Other Than Psc101mentioning
confidence: 91%
“…IncQ plasmids contain replicon and mobilization modules in the backbone (24). The RSF1010, R1162, and R300B plasmids isolated independently from Escherichia coli, Pseudomonas aeruginosa, and Salmonella enterica serovar Typhimurium, respectively, are the best-characterized members of this group (4, 25, 26). In each of these plasmids, the minimal replicon consists of repA, repB and repC genes, which encode helicase, primase, and iteron-binding proteins, respectively, and an oriV region containing the origin of replication (27).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the vectors for cloning into methylotrophic bacteria have been constructed on the basis of RSF 1010 and other plasmids of the Inc P4 incompatibility group [2, 3,9]. The small multicopy plasmid RSF 1010 [4] is stably maintained in a wide range of gram-negative bacteria [5, 61 and can efficiently be mobilized by various conjugative plasmids [7].…”
Section: Introductionmentioning
confidence: 99%